2007
DOI: 10.1089/neu.2007.0294
|View full text |Cite
|
Sign up to set email alerts
|

Progesterone Improves Acute Recovery after Traumatic Brain Injury in the Aged Rat

Abstract: Recent evidence has demonstrated that treatment with progesterone can attenuate many of the pathophysiological events following traumatic brain injury (TBI) in young adult rats, but this effect has not been investigated in aged animals. In this study, 20-month-old male Fischer 344 rats with bilateral contusions of the frontal cortex (n = 4 per group) or sham operations received 8, 16, or 32 mg/kg of progesterone or vehicle. Locomotor activity was measured at 72 h to assess behavioral recovery. Brain tissue was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
137
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 153 publications
(150 citation statements)
references
References 46 publications
12
137
0
1
Order By: Relevance
“…The current findings, demonstrating progesterone's ability to regulate the DNA damage response, cell proliferation, and blood vessel remodeling following TBI, are novel and have not been previously described. The decreased dosedependent effect of progesterone on functional recovery and inflammatory markers in experimental TBI models (Cutler et al, 2007;Goss et al, 2003) is consistent with our findings of a decreased effect on gene expression at the higher dose of progesterone 7 days post-TBI. Currently, it is not known whether high-dose progesterone is more beneficial than lowdose progesterone at 7 days.…”
Section: Figsupporting
confidence: 91%
See 1 more Smart Citation
“…The current findings, demonstrating progesterone's ability to regulate the DNA damage response, cell proliferation, and blood vessel remodeling following TBI, are novel and have not been previously described. The decreased dosedependent effect of progesterone on functional recovery and inflammatory markers in experimental TBI models (Cutler et al, 2007;Goss et al, 2003) is consistent with our findings of a decreased effect on gene expression at the higher dose of progesterone 7 days post-TBI. Currently, it is not known whether high-dose progesterone is more beneficial than lowdose progesterone at 7 days.…”
Section: Figsupporting
confidence: 91%
“…It was found that the 8 and 16 mg/kg doses improved water maze performance compared to the 32 mg/ kg dose, and that none of the doses significantly decreased lesion size (Goss et al, 2003). Similarly, a study in older rats also found that the 32 mg/kg dose resulted in significantly fewer beneficial effects on inflammatory factors than 8 mg/kg and 16 mg/kg at 48 h post-injury (Cutler et al, 2007).…”
Section: T He Centers For Disease Control and Preventionmentioning
confidence: 95%
“…Rats were subjected to sham surgeries (n ¼ 4) or TBI (n ¼ 5) according to procedures described elsewhere (Cutler et al, 2007). Briefly, the rats were initially anesthetized under 5% isoflurane anesthesia for 3 min, 45 s, and nitrous oxide (700 mmHg=min) with oxygen (400 mmHg=min) as a carrier.…”
Section: Surgeriesmentioning
confidence: 99%
“…Briefly, the protein concentration in the supernatant was measured using Coomassie blue reagent, and the Cx, HT, and AP (not SME) homogenates were used to prepare the samples for SDS-PAGE, as described elsewhere (Cutler et al, 2007), to a final concentration of 1.2 mg=mL. AP Western samples with a concentration of 0.12 mg=mL were used for the assay of GH.…”
Section: Tissue Processingmentioning
confidence: 99%
“…Multifactorial effects of progesterone include inhibition of inflammatory cytokines, reduced levels of inflammation-related factors, prevention of excitotoxicity, reduction of apoptosis, and control of vasogenic edema. [7][8][9][10] The progesterone receptor plays a key role in these neuroprotective effects. 11 A total of 20 research groups working with four species and 22 different models have found neuroprotective effects of progesterone in more than 180 experimental pharmacologic studies.…”
mentioning
confidence: 99%